2019
DOI: 10.1186/s42077-019-0022-1
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam–ketamine versus dexmedetomidine–ketamine combinations for anesthesia of pediatric patients undergoing cardiac catheterization

Abstract: Background: The aim of the current study was to compare the effects of midazolam-ketamine versus dexmedetomidine-ketamine combinations on hemodynamics, sedation level, and recovery period in pediatric patients undergoing cardiac catheterization for hemodynamic study. Patients and methods: Fifty pediatric patients undergoing cardiac catheterization for hemodynamic study were enrolled in the current study. Patients were randomly distributed to one of two equal groups: midazolamketamine group (group M) and dexmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The sample size was calculated using the STATA program, setting the type-1 error (α) at 0.05 and the power (1-β) at 0.8. the results from the previous study [11] showed that the ketamine consumption among the dexmedetomidine/ketamine group was 1.35 ± 0.75 mg/kg/h while among the midazolam/ ketamine group was 2.15 ± 1.43 mg/kg/h with a p-value less than 0.05. According to these values, a sample size of 35 cases per group is enough.…”
Section: Sample Size Justificationmentioning
confidence: 74%
“…The sample size was calculated using the STATA program, setting the type-1 error (α) at 0.05 and the power (1-β) at 0.8. the results from the previous study [11] showed that the ketamine consumption among the dexmedetomidine/ketamine group was 1.35 ± 0.75 mg/kg/h while among the midazolam/ ketamine group was 2.15 ± 1.43 mg/kg/h with a p-value less than 0.05. According to these values, a sample size of 35 cases per group is enough.…”
Section: Sample Size Justificationmentioning
confidence: 74%
“…It was shown that ketamine in the combination with dexmedetomidine induced good efficacy and sedation, less intraoperative use of anesthetics, less arrhythmias and shorter recovery time in pediatric patients during cardiac catheterizations. Bolus injection which contained ketamine (1 mg/kg) and dexmedetomidine (1 mg/kg) was superior comparing to midazolam-ketamine combination in pediatric patients [36,37]. In adults, the common intravenous dose of ketamine for induction of anesthesia is 0.5-2 mg/kg, and the maintaince the dose is 1-2 mg/min.…”
Section: Anesthesiamentioning
confidence: 99%
“…It was shown that ketamine in combination with dexmedetomidine induced good efficacy and sedation, less intraoperative use of anesthetics, less arrhythmias and a shorter recovery time in pediatric patients during cardiac catheterizations. A bolus injection which contained ketamine (1 mg/kg) and dexmedetomidine (1 mg/kg) was superior compared to a midazolam–ketamine combination in pediatric patients [ 64 , 65 ]. In adults, for induction, ketamine is given intravenously at doses of 0.5–2 mg/kg, with a maintenance dose of 1–2 mg/min.…”
Section: Anesthesiamentioning
confidence: 99%